(untitled) (Research, Society and Development, 2020)
Vitamin D (VD) is a steroid hormone with multiple biological functions in the body and its activity requires the binding to the receptor named VDR. VDR polymorphisms seems to be involved in the development of several types of cancer. Herein we performed the genotyping of two VDR polymorphisms (Fok I and Taq I) in MCF-7 breast cancer and U87-MG glioblastoma (GBM) cell lines and investigated the antiproliferative effect of the VD analog cholecalciferol. Polymorphisms were identified by PCR-RFLP and the effect of VD was determined by viability and clonogenic assays. VD inhibited the growth of both tumor cells in vitro. MCF-7 cells were more sensitive than U87-MG cells at concentrations ranging from 0.1nM to 1000nM. The same primer pairs used for PCR amplification of VDR gene in MCF-7 failed to amplify a fragment of expected size in the U87-MG cell line. VDR Fok I and Taq I polymorphisms in breast cancer MCF-7 cells were characterized as FF (CC) and TT respectively. The absence of amplification of VDR gene fragment in U87-MG suggests a possible chromosomal rearrangement and/or impairment of gene expression of VDR which could interfere in the sensitivity of this cell line to vitamin D.